1996
DOI: 10.3168/jds.s0022-0302(96)76381-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Intake and Production of Cows Offered Ensiled Alfalfa with Higher Neutral Detergent Fiber Digestibility

Abstract: The objective of this study was to determine the effect of forage fiber digestibility as part of a total mixed diet on intake and production of cows with intakes that were likely limited by rumen fill, using treatments that were not confounded by fiber source, concentrate, or ratio of forage to concentrate. Two alfalfa silages with similar NDF concentrations (40%) but different NDF digestibilities (40 vs. 45% after 24 h of in vitro fermentation) were harvested, mixed with concentrate to achieve diets containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
1
38
2
1
Order By: Relevance
“…The chemical and physical characteristics of NDF are both important in dairy diets to maintain normal milk production and normal chewing activities (Beauchemin et al 1994;Dado and Allen 1996). However, only the chemical requirement for NDF is presently considered by the NRC (1989).…”
Section: Okine Et Al -Forage Source and Chewing Activity In Cows 257mentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical and physical characteristics of NDF are both important in dairy diets to maintain normal milk production and normal chewing activities (Beauchemin et al 1994;Dado and Allen 1996). However, only the chemical requirement for NDF is presently considered by the NRC (1989).…”
Section: Okine Et Al -Forage Source and Chewing Activity In Cows 257mentioning
confidence: 99%
“…Thus, in spite of similar DMI, the NDF intake of cows fed the bromegrass diet was higher than that of cows fed the alfalfa diet reflecting the greater NDF concentration in bromegrass. Miller et al (1990) and Dado and Allen (1996) suggested that the rate of NDF digestion, amount of NDF and digestibility of NDF in diets can affect feed intake. In this study NDF digestion was not affected by dietary treatment (data not shown).…”
Section: Feed Intake and Milk Production And Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effects of enhanced IVFD on productivity of lactating dairy cows have been reported for corn silage (Thomas et al 2001;Neylon and Kung, Jr. 2003;Ivan et al 2005), sorghum silage (Grant et al 1995;Aydin et al 1999;Oliver et al 2004), and alfalfa silage (Dado and Allen 1996). Whole-plant barley silage (WPBS) is the primary forage used by dairy producers in western Canada, but little is known about factors affecting IVFD and its effects on animal performance.…”
mentioning
confidence: 99%
“…When multiple models had similar likelihood values, the model associated with the least Bayesian information criteria was chosen as the best prediction model. All the meta-analyses were Castle and Watson, 1973;Castle and Thomas, 1975;Little et al, 1976;Holter et al, 1982;Murphy et al, 1983;Stockdale and King, 1983;Andersson et al, 1984;Woodford et al, 1984;Andersson, 1985;Janicki et al, 1985;Nocek and Braund, 1985;Richards, 1985;Anderson, 1987;Gorewit et al, 1989;Holter et al, 1990Shalit et al, 1991;Bahman et al, 1993;Dado and Allen, 1993, 1995, 1996Silanikove et al, 1997;Dahlborn et al, 1998;Dewhurst et al, 1998;Muller et al, 1994;Mooney and Allen, 1997;Burgos et al, 2001;Osborne et al, 2002aOsborne et al, , 2009Voelker and Allen, 2003;Cottee et al, 2004;Meyer et al, 2004;Taylor and Allen, 2005;Harvatine and Allen, 2006;Chaiyabutr et al, 2007Chaiyabutr et al, , 2008Thomas et al, 2007;Cardot et al, 2008;Kume et al, 2008Kume et al, , 2010Longuski et al, 2009;Kramer et al, 2009;…”
mentioning
confidence: 99%